Nilai Praktik Ekonomi Islam pada Lembaga Bisnis Syariah - Wahyuni, Lisa; Sukti, Surya (UNIVERSITAS SERAMBI MEKKAH, 2025)
Sharia business institutions, such as sharia banks, sharia financing companies, and sharia insurance, operate based on Islamic principles, avoiding usury, gharar, and practices that are not in accordance with sharia. These institutions aim to achieve falah (prosperity in this world and the hereafter) through transparency, justice and collaboration in transactions.Islamic economic values ​​such as justice, balance, transparency, social responsibility, desire, as well as ethics and morality guide economic activities. This system prioritizes fair distribution of wealth, harmony between individuals and society, as well as environmentally friendly and moral business practices.Application of Islamic economic values ​​in sharia business institutions, such as PT. BPRS Jabal Nur Surabaya, emphasizes the importance of governance based on sharia principles, such as transparency, justice and ethics. Operations that focus on poverty, fairness in services, and avoidance of usury and gharar, create public trust and support social welfare.